Impressions on European physiology education and research—A quick view from the Portuguese experience - Luís Monteiro Rodrigues (Physiological Reports)
Abstract The Bologna Process and the European Higher Education Area (EHEA) are celebrating 25 years of free mobility and career opportunities. Despite its progress, disparities exist in the effectiveness of this initiative across EHEA countries. Physiology is a mandatory component of health science curricula but lacks standardized educational benchmarks, leading to limited societal awareness and professional opportunities. In contrast, there is a different dynamic in the USA, where physiology is a profession with growing opportunities. Within Europe, national scientific societies are actively promoting physiology education and research but societal awareness and physiology related knowledge and opportunities are still limited. A recent study on the Portuguese reality revealed that while physiology is taught at many institutions, there is significant variability in hands‐on training between universities and technical colleges. Notably, only a small percentage of faculty have published in physiology journals, suggesting a diluted identity for the discipline. Challenges in harmonization and training reflect a need for stronger collaboration among scientific organizations to improve physiology teaching and research across Europe. By addressing these issues, the future of physiology can be strengthened, ensuring better recognition and professional development for physiologists in the EHEA.